Celebrating the 20th anniversary of the establishment of the Faculty of Medicine at the University of Maribor - Pahor, Dušica (Acta Medico-Biotechnica, 2023)
After many years of various endeavours and efforts, the Faculty of Medicine at the University of Maribor (the MF UM) was established in 2003. All of us who were fortunate enough to have taken part in this, remember this event fondly. After many decades the goal was achieved—a new Faculty of Medicine has emerged, the second in our country.